Viral determinants predicting hepatitis B surface antigen (HBsAg) seroclearance in HIV‐/HBV‐coinfected patients. Issue 7 (24th September 2013) - Strassl, R.; Reiberger, T.; Honsig, C.; Payer, B. A.; Mandorfer, M.; Grabmeier‐Pfistershammer, K.; Rieger, A.; Kundi, M.; Grundtner, P.; Peck‐Radosavljevic, M.; Popow‐Kraupp, T.
Summary The aim of this retrospective study was the identification of clinically useful viral determinants for the prediction of hepatitis B surface antigen (HBsAg) seroclearance and sustained virological response in hepatitis B virus/human immunodeficiency virus (HBV‐/HIV)‐coinfected patients receiving HBV‐active combined antiretroviral therapy (cART). Quantification of HBsAg, HBeAg and HBV DNA before and after initiation of HBV‐active cART in a cohort of 59 HIV‐/HBV‐coinfected patients was performed. Calculations of receiver operating characteristics (ROC) and Kaplan–Meier analysis were used for the identification of predictors of HBsAg seroclearance for HBeAg‐positive [HBeAg(+); n = 36] and HBeAg‐negative [HBeAg(−);n = 23] patients. HBeAg(+) patients with an HBsAg on‐treatment decline ≥1 log IU/mL per year achieved higher HBsAg loss rates (P = 0.0294), whereas the quantification of HBeAg had no predictive value for HBsAg seroclearance. Among HBeAg(−) patients, a pretreatment baseline cut‐off level of HBsAg ≤100 IU/mL was highly predictive for HBsAg seroclearance. No significant influence of the HBV genotype on HBsAg seroclearance was observed among the entire cohort. Quantitative determination of HBsAg provides a clinically useful viral parameter for the prediction of HBsAg seroclearance both in HBeAg(+) and HBeAg(−) HIV‐/HBV‐coinfected patients receiving HBV‐active cART.